2024
DOI: 10.3390/biology13040206
|View full text |Cite
|
Sign up to set email alerts
|

Modular Hub Genes in DNA Microarray Suggest Potential Signaling Pathway Interconnectivity in Various Glioma Grades

Marco A. Orda,
Peter Matthew Paul T. Fowler,
Lemmuel L. Tayo

Abstract: Gliomas have displayed significant challenges in oncology due to their high degree of invasiveness, recurrence, and resistance to treatment strategies. In this work, the key hub genes mainly associated with different grades of glioma, which were represented by pilocytic astrocytoma (PA), oligodendroglioma (OG), anaplastic astrocytoma (AA), and glioblastoma multiforme (GBM), were identified through weighted gene co-expression network analysis (WGCNA) of microarray datasets retrieved from the Gene Expression Omn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Furthermore, a recent study has also discovered an increased risk for uterine sarcoma and endometrial cancer following endometriosis or pelvic inflammatory disease (PID) [ 31 ]. WGCNA analysis [ 32 ] was applied to scan for existing disease networks in gynecological cancers, represented by the OC, CC, and EC datasets with regard to the EM dataset. The functional annotation and pathway enrichment analysis through DAVID gene ontology has shown that most of the highly preserved modules, cyan, purple, midnightblue, and tan modules, were primarily involved with transcription dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study has also discovered an increased risk for uterine sarcoma and endometrial cancer following endometriosis or pelvic inflammatory disease (PID) [ 31 ]. WGCNA analysis [ 32 ] was applied to scan for existing disease networks in gynecological cancers, represented by the OC, CC, and EC datasets with regard to the EM dataset. The functional annotation and pathway enrichment analysis through DAVID gene ontology has shown that most of the highly preserved modules, cyan, purple, midnightblue, and tan modules, were primarily involved with transcription dysfunction.…”
Section: Discussionmentioning
confidence: 99%